A CFD ANALYSIS IN SOLIDWORKS FLOW SIMULATION FOR TWO MIXING FLUIDS WITH DIFFERENT TEMPERATURES IN NOZZLES - IONEL OLARU (Journal of Engineering Studies and Research)
The heat can have a direct impact on the mechanical elements by creating deformations and by causing the induction of additional stress in them. In designing of the heat exchangers or for the electronic components, the temperature changes for structural analysis as well as structural performance of thermal impact for the entire element must be analyzed. The study from this paper proposes an analysis and a simulation of flow through the convergent-divergent nozzle type to optimize the inlet of warm fluid to have minimum impact on the nozzle walls This analysis will be performed with a computer program specialized in complex analysis of Computational Fluid Dynamics (CFD), which will also take into account the fluid temperature and its influence throughout the system.